Cash conversion cycle and financial performance: evidence from listed manufacturing firms In Sri Lanka - Balagobei, S.; Anandasayanan, S. (University of Jaffna, 2020)
Cash Conversion Cycle (CCC) is considered as an effective measure of firms’ working capital management. It is also a prolific performance measure for assisting how well a company is managing its working capital. This study aims to investigate the influence of CCC on the financial performance of listed companies in Sri Lanka. The data was gathered by using secondary sources, whereas Pearson’s correlation and multiple regression analysis were employed to analyse the data for the period of 2011 to 2018. The results of the empirical finding show that there is a strong negative influence of the cash conversion cycle on the financial performance of listed companies. Therefore, the study suggests that managers of listed companies can create a positive value for the shareholders by reducing the cash conversion cycle to a possible minimum level and also accounts receivables should be kept at an optimal level.
Keywords: Cash conversion cycle; Financial Performance; Working capital